2011
DOI: 10.1074/jbc.m110.213470
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylethanolamines Modified by γ-Ketoaldehyde (γKA) Induce Endoplasmic Reticulum Stress and Endothelial Activation

Abstract: Peroxidation of plasma lipoproteins has been implicated in the endothelial cell activation and monocyte adhesion that initiate atherosclerosis, but the exact mechanisms underlying this activation remain unclear. Lipid peroxidation generates lipid aldehydes, including the ␥-ketoaldehydes (␥KA), also termed isoketals or isolevuglandins, that readily modify the amine headgroup of phosphatidylethanolamine (PE). We hypothesized that aldehyde modification of PE could mediate some of the proinflammatory effects of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
74
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(80 citation statements)
references
References 53 publications
5
74
0
Order By: Relevance
“…In addition, previous experimental evidence obtained in in vitro studies has suggested that IsoLG-PE may have a limited incorporation into the cells leading to the need of employing higher doses in order to elicit biological effects [20]. Based on these considerations, we decided to employ a range of concentrations (picomolar or nanomolar concentrations) which are likely to be reached in conditions of sustained oxidative stress in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, previous experimental evidence obtained in in vitro studies has suggested that IsoLG-PE may have a limited incorporation into the cells leading to the need of employing higher doses in order to elicit biological effects [20]. Based on these considerations, we decided to employ a range of concentrations (picomolar or nanomolar concentrations) which are likely to be reached in conditions of sustained oxidative stress in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…One of the triggers for autophagy is ER stress, and secondary activation of the unfolded protein response (UPR) [47,48]. Indeed activation of the unfolded protein response has previously been described in HUVEC cells following exposure to IsoLG [20].…”
Section: Exposure To Isolg Promotes Increased Autophagy In Hscmentioning
confidence: 99%
See 3 more Smart Citations